2017
DOI: 10.1080/15384101.2017.1317416
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA lnc-sox5 modulates CRC tumorigenesis by unbalancing tumor microenvironment

Abstract: Long non-coding RNAs (LncRNAs) have been recently regarded as systemic regulators in multiple biologic processes including tumorigenesis. In this study, we observed the expression of lncRNA lnc-sox5 was significantly increased in colorectal cancer (CRC). Despite the CRC cell growth, cell cycle and cell apoptosis was not affected by lnc-sox5 knock-down, lnc-sox5 knock-down suppressed CRC cell migration and invasion. In addition, xenograft animal model suggested that lnc-sox5 knock-down significantly suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…Wu et al reported that lnc-sox5 was upregulated during the tumorigenesis of colorectal cancer (CRC). Additionally, the absence of lnc-sox5 did not affect the growth of tumor cells in immunodeficient mice, but significantly suppressed tumorigenesis in immunocompetent mice (50). Flow cytometry analysis suggested that the knock down of lnc-sox5 promoted the infiltration and the cytotoxicity of CD3 + CD8 + CTLs in tumors in immunocompetent mice.…”
Section: Expression Of Molecules In Tumor Cellsmentioning
confidence: 92%
“…Wu et al reported that lnc-sox5 was upregulated during the tumorigenesis of colorectal cancer (CRC). Additionally, the absence of lnc-sox5 did not affect the growth of tumor cells in immunodeficient mice, but significantly suppressed tumorigenesis in immunocompetent mice (50). Flow cytometry analysis suggested that the knock down of lnc-sox5 promoted the infiltration and the cytotoxicity of CD3 + CD8 + CTLs in tumors in immunocompetent mice.…”
Section: Expression Of Molecules In Tumor Cellsmentioning
confidence: 92%
“…Extensive and in-depth research on the TME should importantly involve noncoding RNAs (ncRNAs), such as microRNAs (miRNAs) [10][11][12] and long ncRNAs (lncRNAs) [13][14][15]. With the broad application of highthroughput RNA sequencing (RNA-seq), numerous circular RNAs (circRNAs) have been identified and characterized in humans and other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lncRNAs have been identified as CRC oncogenes or tumor suppressors [ 23 , 24 , 25 ]. FEZF1-AS1 downregulation inhibits cell proliferation, migration, and invasion, suggesting that this lncRNA promotes CRC tumorigenesis and progression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%